2021
DOI: 10.1002/lary.29480
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Testing before Pediatric Adenotonsillectomy for Severe and Very Severe Obstructive Sleep Apnea Syndrome

Abstract: Objectives/Hypothesis: Adenotonsillectomy is first-line treatment for pediatric obstructive sleep apnea syndrome (OSAS) when not otherwise contraindicated. There is concern severe OSAS increases risk of comorbid cardiopulmonary abnormalities, such as ventricular hypertrophy or pulmonary hypertension, which preoperative testing could detect. Our objective is to determine if there is a severity of pediatric OSAS where previously undetected cardiopulmonary comorbidities are likely.Study Design: Retrospective char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Recent studies on the prevalence of PH in children with OSA show variable results, mostly with findings similar to ours with a low prevalence of PH in this group of children; similar to our results, the studies by Clements et al [ 44 ] and Teplitzky et al [ 45 ] found no association between the degree of severity of OSA and abnormal echocardiographic findings. Similarly, a systematic review of echocardiographic findings in children with obstructive sleep apnea in the pediatric population found no consistent results; of the 13 studies that met the inclusion criteria, only 2 measured the TRV, and of these, only one found a positive correlation with AHI([ 46 ]).…”
Section: Discussionsupporting
confidence: 89%
“…Recent studies on the prevalence of PH in children with OSA show variable results, mostly with findings similar to ours with a low prevalence of PH in this group of children; similar to our results, the studies by Clements et al [ 44 ] and Teplitzky et al [ 45 ] found no association between the degree of severity of OSA and abnormal echocardiographic findings. Similarly, a systematic review of echocardiographic findings in children with obstructive sleep apnea in the pediatric population found no consistent results; of the 13 studies that met the inclusion criteria, only 2 measured the TRV, and of these, only one found a positive correlation with AHI([ 46 ]).…”
Section: Discussionsupporting
confidence: 89%
“…Tables 1 and 2 show studies conducted over the past 20 years, each with a different research purpose and study methods. The available studies can be classified as observational studies (n.2) [16,17], retrospective studies (n.3) [18][19][20], cross-sectional studies (n.4) [21][22][23][24], comparative studies (n.2) [25,26], prospective studies (n.8) [27][28][29][30][31][32][33][34], and clinical trial (n.1) [35].…”
Section: Marangu D Et Al (2014) [24]mentioning
confidence: 99%
“…The minimum number of children in one study was 23 [33], while the maximum number in a study was 620 [19]. The minimum age was 2.5 years [27], and the maximum was 21 years [20]. The authors of these studies used various methods to assess OSA and its effects on the cardiovascular system in children.…”
Section: Marangu D Et Al (2014) [24]mentioning
confidence: 99%
See 2 more Smart Citations